POSTPROCESSOR AND MACRO PROGRAM FOR CALCULATION OF THE DISPLACEMENTS OF THE WORKING COORDINATE SYSTEMS WHEN WORKING BY THE METHOD 3 + 2 AXES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Тhis article discusses the possibility of developing a postprocessor and macro program for automatic calculation and input of the displacements in the working coordinate systems when working by the method 3 + 2 axes. The ability to take the information from the CL Data file and its subsequent use by a macro program for certain calculations is used. For this purpose, a generalized G-POST postprocessor and a specialized FIL language are used.